Alleviation of arsenic accumulation in rice by applying silicon-rich rice husk residues in Bangladesh soil - Mamud, A; Saha, B; Hossain, SA; Chowdhury, MTA (Bangladesh Journal of Scientific and Industrial Research, 2021)
While the accumulation of arsenic in rice (Oryza sativa L.) has been highlighted as a major concern in Bangladesh, sustainable measures are critically needed to reduce the uptake of arsenic by rice plants. In the present study, a pot-experiment was conducted using a Boro rice variety (BRRI dhan-29) in two geomorphologically different soils from Holocene floodplains and Pleistocene terraces, in which silicon-rich fresh rice husk (FRH) and rice husk ash (RHA) were applied, as silicon fertilisers, in the soils at the rate of 1% (w/w) of rice residue:soil.In the Holocene floodplain soils, the application of FRH was found to decrease arsenic in grain, husk and straw by 42, 56 and 51%, respectively, whereas the soil incorporation of RHA decreased arsenic in grain, husk and straw by 26, 37.5 and 36%, respectively. In the Pleistocene terrace soils, the application of FRH reduced the grain, husk and straw arsenic by 38, 38 and 44%, respectively, whereas the RHA decreased the grain, husk and straw arsenic by 26, 30 and 29%, respectively. Fresh rice husk was found to be more effective in alleviating arsenic accumulation in rice than RHA. In both the Holocene floodplain and Pleistocene terrace soils, the grain concentrations of calcium, phosphorus, silicon, and zinc were found to be increased with the decrease of arsenic in the grain due to the use of FRH and RHA. The present study suggests that silicon-rich rice husk residue scan be used as silicon fertilisers to reduce arsenic accumulation in rice in Bangladesh. Bangladesh J. Sci. Ind. Res.56(3), 195-206, 2021